Paleoecology of an Interglacial Peat Deposit, Nuyakuk, Southwestern Alaska, U.S.A. - Elias, Scott; Short, Susan (Géographie physique et Quaternaire, 1992)
ABSTRACTThis paper reports the presence of interglacial beetle and pollen assemblages within a Pleistocene peat deposit exposed along the Nuyakuk River of southwestern Alaska. The fossil beetle assemblages contain a number of species not previously identified from eastern Beringian fossil assemblages. The Nuyakuk interglacial deposits are exposed within a 6-m-high terrace along the river, about 4 km beyond the moraine of the penultimate glaciation. Interglacial peat lies within the lowermost meter of the bluff and is overlain by fluvial gravel and loess. Insect fossils were extracted from five peat samples, yielding sixty-seven identified beetle taxa. The insect faunal diversity of the Nuyakuk assemblages is comparable to that found in regional Holocene peat samples. In contrast to assemblages of similar age from interior eastern Beringia, the Nuyakuk fauna contains significant numbers of aquatic, hygrophilous and riparian taxa. Four pollen samples from the Nuyakuk site were analyzed, providing spectra dominated by a few taxa, notably Alnus, Betula, Picea, Gramineae, Cyperaceae, Filicales, and Sphagnum, suggesting a rich alder-birch shrub tundra not much different from the modern regional vegetation. The pollen and insect fossil records also suggest climatic conditions similar to modern.